Analysis of the epidemiological of acute cases of Chagas Disease in Brazil between 2019 and 2022 (Research, Society and Development, 2024)
The objective of this study was to analyze the acute cases of this disease in the country, between the years 2019 and 2022. This is an ecological study, carried out with secondary data from the Department of Information Technology of the Unified Health System (DATASUS), coming from the Notifiable Diseases Information System (SINAN). The period from January 2019 to December 2022 was chosen due to the availability of the data at the time of collection. The variables chosen to compose the study were: Year of notification, total cases per year, sex, race, age group, confirmation criteria, clinical evolution and region of residence. After collecting the variables, they were tabulated in Microsoft Excel 2019 and the absolute and relative frequency of each variable was calculated. Referring to the data presented, it can be stated that the highest frequency of new cases was in men, dark-skinned individuals, residents of the northern region of the country, most diagnoses were made based on laboratory tests and this pathology has a low mortality rate. The data presented can help health managers, allowing the recognition of the main factors that contribute to minimizing new infections by Chagas disease.